Big Fishery, Big Data, and Little Crabs: Using Genomic Methods to Examine the Seasonal Recruitment Patterns of Early Life Stage Dungeness Crab (Cancer magister) in the California Current Ecosystem - Lee, Elizabeth M. J.; O’Malley, Kathleen G. (Frontiers in Marine Science, 2020)
The California Current Ecosystem (CCE) is a dynamic marine ecosystem from which many socioeconomically important fisheries species are harvested. Here, a genotyping-by-sequencing (GBS) approach was used to examine genomic variation in an early life stage (megalopae) of the Dungeness crab (Cancer magister), which constitutes the most valuable single-species commercial fishery in the CCE. Variation in abundance and timing of megalopae recruitment has been extensively studied for over two decades in Coos Bay, Oregon, United States. Within the CCE, documented timing of Dungeness crab life history events indicates that coastal megalopae recruitment is expected to occur April through July; however, long-term studies in Coos Bay have observed late-season recruitment from August to October. Based on variation at 1,913 presumably neutral loci, evidence was found for weak, yet significant differentiation (FST estimate = 0.0011) between the 2014 expected-season recruits (n = 47) and late-season recruits (n = 47) collected in Coos Bay. However, two putatively adaptive loci with a high FST estimate (0.2036) between expected-season and late-season recruits were identified. These findings support the hypothesis that expected-season and late-season megalopae recruiting to Coos Bay within the same year may have originated from different locations or from different breeding groups. Understanding marine species connectivity between ecosystems is important when considering how future changes in ocean conditions may impact fishery harvests.